Kerentanan Rumah Tangga Petani Padi Sawah Tadah Hujan (Studi Kasus Di Kecamatan Kroya Kabupaten Indramayu) - Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa; Charina, Anne (Universitas Galuh, 2024)
Changes in environmental conditions pose a significant threat to rice production in Kroya Sub-district, Indramayu Regency, which in turn affects the vulnerability of farmer households. This study aims to analyze the vulnerability context faced by wet-rice farmer households in Kroya District, Indramayu Regency, using a qualitative design and case study techniques. The study collected primary data from 50 informants and participants through observation and in-depth interviews. The data was analyzed descriptively using three simultaneous activities: data reduction, data presentation, and conclusion drawing. The results indicate that vulnerabilities are related to shocks and seasons, and there are subjective factors in understanding the context of vulnerability. To address the vulnerability, farmer households implement adaptation strategies such as diversifying their income streams in both agricultural and non-agricultural sectors.